Comparison of McKenzie and Cailliet Exercises on Neck Function in Myofascial Pain Syndrome - Aulia Sekar Arum; Ghufroni, Afif; Kuntono, Heru Purbo (Poltekkes Kemenkes Surakarta, 2023)
Background: Myofascial Pain Syndrome (MPS) in the upper trapezius muscle causes pain and limited neck function, which can interfere with work activities. Physiotherapy efforts used to reduce pain and improve neck function include McKenzie Neck Exercise and Neck Cailliet Exercise. The purpose of this study was to determine the difference in the effects of McKenzie Neck Exercise and Neck Cailliet Exercise on neck functional ability in workers with MPS of the upper trapezius muscle. Methods: This study used a quasi-experimental design with a two-group pre- and post-test design. Sampling was conducted using simple random sampling of 30 employees of PT Iskandar Indah Printing Textile who met the inclusion criteria. The subjects were divided into two groups, namely group I, which received McKenzie Neck Exercise (n=15), and group II, which received Neck Cailliet Exercise (n=15). The intervention was given twice a week for three weeks. The research instrument used the Neck Disability Index (NDI) to measure neck functional ability. Data analysis was performed using the Wilcoxon test, paired t-test, and independent t-test. Results: The test results showed a significant improvement in neck functional ability in both groups (group I p=0.001; group II p=0.000). The between-group difference test showed a p-value of 0.004 (p<0.05), which means there was a significant difference between the two exercises. Conclusion: Both exercises were effective in improving neck function, but the McKenzie Neck Exercise was more effective than the Neck Cailliet Exercise. The McKenzie Neck Exercise can be recommended as a more optimal physiotherapy intervention to improve neck function in workers with upper trapezius muscle Myofascial Pain Syndrome.